Use of tannin-based coagulant and chlorine dioxide in treating brewing water: reduction of trihalomethanes and impact on physicochemical and sensory quality. Issue 10 (19th October 2022) - Caon, Arliana; Conte, Gilmar; Skoronski, Everton
Abstract: This study aimed to evaluate an alternative to reduce trihalomethane (THM) formation in brewing water. THM affects the organoleptic properties of water and, consequently, the produced beer. Water treatment based on common chemicals such as alum and free chlorine could potentially form THM. Therefore, we studied the replacement of chemicals used in water treatment: aluminum sulfate by a tannin-based coagulant and sodium hypochlorite by chlorine dioxide. Experimentally, jar tests were conducted, and the role of coagulants and oxidizing agents was evaluated for: the removal of apparent color, turbidity, natural organic matter (NOM) and microorganisms; the formation of trihalomethanes (THM); and the sensory quality of the water. Using tannin-based coagulant with chlorine dioxide was associated with the lowest THM in treated water (1.7 µg/L) and higher satisfaction in the sensory analysis. However, using these chemicals make the water treatment more expensive than the current strategy. Overall, using the tannin-based coagulant and chlorine dioxide treatment is an alternative to produce water with a lower THM concentration, better physical-chemical, and sensory quality. These findings motivate further brewing experiments and a deeper economics evaluation considering the process's sustainability.